Predictive and Prognostic Role of Tumor‐Infiltrating Lymphocytes for Early Breast Cancer According to Disease Subtypes: Sensitivity Analysis of Randomized Trials in Adjuvant and Neoadjuvant Setting. (10th February 2016) - Carbognin, Luisa; Pilotto, Sara; Nortilli, Rolando; Brunelli, Matteo; Nottegar, Alessia; Sperduti, Isabella; Giannarelli, Diana; Bria, Emilio; Tortora, Giampaolo
Abstract : Background: The role of tumor‐infiltrating lymphocytes (TILs) in breast cancer (BC) is still an issue for clinical research. Toward this end, a sensitivity analysis of neoadjuvant and adjuvant randomized clinical trials was performed according to disease subtypes. Methods: Pathological complete responses (pCRs) after neoadjuvant treatment according to the presence or absence of lymphocyte‐predominant BC (LPBC) were extracted and cumulated as odds ratios (ORs) by adopting a random‐effects model by subtype. Overall survival hazard ratios as a function of 10% incremental values of stromal TILs (sTILs) in adjuvant trials were extracted. The interaction test was adopted to determine the differential effect according to the subtype. Results: Eight trials (5, 514 patients) were identified. With regard to neoadjuvant setting (4 studies), a significant interaction ( p < .0001) according to LPBC was found. The presence of LPBC was associated with a 29.5% increase in pCR rate compared with non‐LPBC ( p < .0001). The pCR rate was significantly higher in patients with LPBC in triple‐negative BC (TNBC) and HER2‐positive BC settings, with an absolute difference of 15.7% (95% confidence interval [CI], 4.9%–26.2%) and 33.3% (95% CI, 23.6%–42.7%), respectively. With respect to the adjuvant setting (4 studies), a significant interaction ( p < .0001) according to sTILs was found. A survival benefit was more likely to be determined for HER2‐positive BC ( p = .025) and TNBC ( p < .0001), with no statistically significant difference for estrogen receptor‐positive/HER2‐negative disease. Conclusion: Despite the retrospective nature of this analysis, the presence of TILs may represent a robust predictive and prognostic marker for BC, particularly for TNBC and HER2‐positive disease. Implications for Practice: This sensitivity analysis of neoadjuvant and adjuvant randomized clinical trials in breast cancer explores the potential predictive and prognostic role of tumor‐infiltrating lymphocytes (TILs) according to disease subtypes. The level of TILs present at diagnosis was significantly associated with therapeutic efficacy and prognosis in triple‐negative and HER2‐positive early breast cancer. This finding may be useful to include in an "immuno‐score" in the context of traditional classification of breast cancer to be prospectively considered as a stratification factor in future clinical trials. Abstract : The presence of tumor‐infiltrating lymphocytes may potentially be a robust predictive and prognostic marker for breast cancer, particularly for triple‐negative breast cancer and HER2‐positive disease.